LES COUTUMES BONGANDO A L’EPREUVE DE DEVELOPPEMENT - Chico ISAKO LOMA,; King LOMBEYA BOINDA,; Saakul LOMBEYA ESULIA, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The community Bongando living in the Territory of Yahuma, province of Tshopo in Democratic Republic of Congo in relation to the aspects of his custom, a retrograde life, rigid with regard and pratical of development requirements. This study consisted in showing some of these aspects that curbs this people's development. It’s important to note that the entity of Yahuma is inclosed what impacts negatively it’s takeoff. It is then question to think how to place the Bongando customs in the circuit of the development, to analyze their favorable positive aspects favorable to the development, to understand them, to interpret them better to convert them progressively and methodically in instruments of progress, instead of to reject them merely. That making, the analysis suggests the State to apply the national politics concerning customs in order to extract a dynamics of development and encouraging THE initiatives so much individual that collective from african custom encouraging so the development.